2012
DOI: 10.1128/ec.05274-11
|View full text |Cite
|
Sign up to set email alerts
|

SRE1 Regulates Iron-Dependent and -Independent Pathways in the Fungal Pathogen Histoplasma capsulatum

Abstract: Regulation of iron acquisition genes is critical for microbial survival under both iron-limiting conditions (to acquire essential iron) and iron-replete conditions (to limit iron toxicity). In fungi, iron acquisition genes are repressed under iron-replete conditions by a conserved GATA transcriptional regulator. Here we investigate the role of this transcription factor, Sre1, in the cellular responses of the fungal pathogen Histoplasma capsulatum to iron. We showed that cells in which SRE1 levels were diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…Overall regulation of mrsidC, mrsidD and mrsreA as well as the effect of disruption of mrsreA on expression of mrsidD is very similar to what has been observed in other fungi (Hwang et al, 2012;Oberegger et al, 2001;Schrettl et al, 2008). However, the same studies indicated that the range of the genes affected by mrsreA orthologs is species-specific and may include virulence factors beyond iron acquisition.…”
Section: Discussionsupporting
confidence: 78%
“…Overall regulation of mrsidC, mrsidD and mrsreA as well as the effect of disruption of mrsreA on expression of mrsidD is very similar to what has been observed in other fungi (Hwang et al, 2012;Oberegger et al, 2001;Schrettl et al, 2008). However, the same studies indicated that the range of the genes affected by mrsreA orthologs is species-specific and may include virulence factors beyond iron acquisition.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, when iron levels are low, Fep1 is unable to bind chromatin, which results in transcriptional activation of iron transport genes (18). Iron-dependent regulators possessing similar functions and sequences to Fep1 have been identified in several fungi, but not in Saccharomyces cerevisiae (2,6,7,9,15,20). Recent studies have shown that the monothiol glutaredoxin Grx4 is a binding partner of Fep1 and that it plays a critical role in inhibiting Fep1 function when cells undergo a transition from iron-sufficient to iron-limiting conditions (17,23).…”
mentioning
confidence: 99%
“…Consistent with this, exogenous peroxide does not upregulate CatB and CatP expression (28). The only evidence for Histoplasma CatB regulation is increased CATB expression when iron concentrations increase, presumably to prevent the formation of hydroxyl radicals by destroying the predecessor molecule, hydrogen peroxide (78).…”
Section: Discussionmentioning
confidence: 70%